Eksplorasi Fusarium Nonpatogen untuk Pengendalian Penyakit Busuk Pangkal pada Bawang Merah - Umi Sallamatul Isniah; Widodo Widodo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Fusarium oxysporum f. sp. cepae causing basal rot disease is one of an important constrains in shallot productions. Result from several studies showed that non-pathogenic F. oxysporum was very potential to control fusarium basal rot in shallot. This study was conducted to explore non-pathogenic isolates of F. oxysporum from shallot fields which might be effective for controlling basal rot disease. Eighteen out of 21 isolates did not cause any disease symptom, they even promoted shallot growth when inoculated onto bulbs. Three out of 18 selected isolates, i.e. P13a, T14a, and P21a were the most effective isolates in controlling the disease in two consecutive experiments with level of efficacy ranges from 61.2% to 83.3%. This level of efficacy was higher than those of fungicide (benomyl) treatment.